Physiological changes in Jatropha curcas L. seeds during storage - Dias,Denise Cunha Fernandes dos Santos (2016)
Abstract: Oil seeds, such as J. curcas, are more prone to deterioration and consequently to loss of quality during storage. In this context, adequate technics for its preservation are of great importance. This study aimed to evaluate the effects of different environments and packaging for the conservation of J. curcas seeds during twelve months of storage. The seeds were placed in three different types of packaging: a multiwall paper bag (or Kraft paper bag); a cloth bag; and a high-density plastic bag. After this, the seeds were stored in three different conditions: a laboratory (23 ± 3 ºC; 64 ± 11% of RH); a refrigerated room (20 ± 2 oC; 55 ± 5% of RH) and a cold chamber (10 ± 2 oC; 55 ± 5% of RH). Initially and thereafter every three months, the physiological qualities (germination and vigor) of the seeds were evaluated. J. curcas seeds packed in the plastic bags and stored in a cold chamber maintained their germination potential during twelve months. There was a decline in the physiological quality of the seeds stored in the laboratory conditions, independent of the packaging used. It was concluded that the most suitable condition for the storage of J. curcas seeds was packing them in plastic bags, placed in a cold chamber (10 ± 2 oC; 55 ± 5% of RH).